Bilateral Common Iliac Artery Stenosis: A Novel Technique for Deployment of Kissing Iliac Artery Stents. (2015) - Lim, S.C.; Krauss, M.; Khanafer, A.; Ritter, W.
Abstract : Treatment for bilateral proximal iliac disease can be technically challenging, typically requiring simultaneous stent deployment to minimise complications. Up to three operators are required for exact simultaneous deployment of the balloons, contributing to increased operator time and costs. This technical note demonstrates a novel approach to simultaneous stent deployment which uses readily available, inexpensive equipment and minimises the technical difficulty of simultaneous balloon deployment.